Pottery making and communities during the 5th millennium BCE in Fars province, southwestern Iran - Miki, Takehiro, (Archaeopress Archaeology, 2022)
This text explores pottery making and communities during the Bakun period (c. 5000 - 4000 BCE) in the Kur River Basin, Fars province, southwestern Iran, through the analysis of ceramic materials collected at Tall-e Jari A, Tall-e Gap, and Tall-e Bakun A & B.